Why are there so Many Marxism?s? - Prodanov, Vasil (Research Papers, 2018)
The article seeks to answer the question why, from the last decades of the nineteenth century up to now there are so many different types of Marxism claiming to be the most appropriate expression of Marx's ideas. The various approaches to the issue of many Marxisms are  analyzed; the reasons for this diversity; whether there is any "hard core" valid for all types of Marxism; how can the main types of Marxism be distinguished.
Keywords: Marxism; Hard core; Approaches to marxism